Heart failure with preserved ejection fraction: relevance of a dedicated dyspnoea clinic. (16th March 2023) - Verwerft, Jan; Soens, Lucie; Wynants, Jokke; Meysman, Marc; Jogani, Siddharth; Plein, Danielle; Stroobants, Sarah; Herbots, Lieven; Verbrugge, Frederik H
Abstract: Background and aims: Heart failure with preserved ejection fraction (HFpEF) is a syndrome with a heterogeneous presentation. This study provides an in-;depth description of haemodynamic and metabolic alterations revealed by systematic assessment through cardiopulmonary exercise testing combined with exercise echocardiography (CPETecho) within a dedicated dyspnoea clinic. Methods and results: Consecutive patients ( n = 297), referred to a dedicated dyspnoea clinic using a standardized workup including CPETecho, with HFpEF diagnosed through a H2 FPEF score ≥6 or HFA-PEFF score ≥5, were evaluated. A median of four haemodynamic/metabolic alterations was uncovered per patient: impaired stroke volume reserve (73%), impaired chronotropic reserve (72%), exercise pulmonary hypertension (65%), and impaired diastolic reserve (64%) were the most frequent cardiac alterations. Impaired peripheral oxygen extraction and a ventilatory limitation were present in 40% and 39%, respectively. In 267 patients (90%), 575 further diagnostic examinations were recommended (median of two tests per patient). Cardiac magnetic resonance imaging, coronary or amyloidosis workup, ventilation–perfusion scanning, and pulmonology referral were each recommended in approximately one out of three patients. In 293 patients (99%), 929 cardiovascular drug optimizations were performed (median of 3 modifications per patient). In 110 patients (37%), 132 cardiovascular interventions were performed, with ablation as the most frequent procedure. Conclusion: Holistic workup of HFpEF patients within a multidisciplinary, dedicated dyspnoea clinic, including systematic implementation of CPETecho reveals various haemodynamic/metabolic alterations, leading to further diagnostic testing and potential treatment changes in the majority of cases. Structured Graphical Abstract: Structured Graphical Abstract Set-up of the different components of a dedicated dyspnoea clinic for heart failure with preserved ejection fraction. For patients with a confirmed diagnosis according to either the HFA-PEFF score, the H2 FPEF score, or both, downstream implications of testing are presented. CT, computed tomography; ECG, electrocardiogram.